FAKTOR-FAKTOR YANG MEMPENGARUHI MARAKNYA KARYA SASTRA YANG MENGUPAS PERSOALAN SEKSUALITAS DAN TUBUH DALAM KESUSASTRAAN INDONESIA MODERN PADA ERA REFORMASI - Lilis, Nenden (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
Background of this research is a phenomenon in Indonesian literary on reformation era, namely booming literary art thatinvestigate and discuss body and sexuality. This research will reveal factors that influence that phenomenon. With descriptive method, wecollect data by library research and interview, and data processing with literary Sociology approach. Result of this research show that there’s4 factors influencing booming literary works that investigate and discuss body and sexuality on reformation era, 1) reformation era’sgovernment policy; 2) economic factor; 3) ideological factor; and 4) literary canonic politic factor